Hispaniolan boa (Chilabothrus striatus) on vieques island Puerto Rico (2014)
The Hispaniolan (Haitian) Boa, Chilabothrus striatus Fisher 1856, is a large (max snout-vent length [SVL] at least 1865mm) boid species endemic to the island of Hispaniola and nearby satellites (Tolson and Henderson, 1993; Henderson and Powell, 2009). Though previously considered to range into the Bahamas, the Bahamian populations of this species were recently described as an independent lineage warranting specific status (Reynolds et al., 2013). This species is popular in the pet trade, but to-date no known introductions in the Caribbean have occurred outside of the native range (Henderson and Powell, 2009).